If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -11 = 8x + 12 Reorder the terms: -11 + 5x = 8x + 12 Reorder the terms: -11 + 5x = 12 + 8x Solving -11 + 5x = 12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -11 + 5x + -8x = 12 + 8x + -8x Combine like terms: 5x + -8x = -3x -11 + -3x = 12 + 8x + -8x Combine like terms: 8x + -8x = 0 -11 + -3x = 12 + 0 -11 + -3x = 12 Add '11' to each side of the equation. -11 + 11 + -3x = 12 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 12 + 11 -3x = 12 + 11 Combine like terms: 12 + 11 = 23 -3x = 23 Divide each side by '-3'. x = -7.666666667 Simplifying x = -7.666666667
| 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 | | X^2=11x-56 | | 0.5x+0.1(5x)=62.15 | | 4x-20.65=20.1 | | -6f-9f=15 | | 15c+1c+21c= | | 61h=9.3-3.2h | | 7y-10y+6=9 | | x^3-4x+x+6=0 | | 7k-5=19 | | cot^2x=-2 | | 2(4x-3)+10=-6(-x+1)-12 | | 1600-320x+12x^2=0 | | 0.7x-0.6x-9=6 | | 32=1.60x | | K-16=2 | | 2(x+3)+7=9 | | R+R^2=24 | | (3m+8)3+m= | | X^2-31x-30=0 | | 2(9x-1)=-3(5-9x)+2 | | 3n-5=7n+12 | | 2x^2*3y= | | e/0.6-9=16 | | (0)=-14x+7 | | 6(7x+2)=42x+12 | | 6x+8x-57=95-5x | | 5=bx+c | | -14x^0+46x-12=0 | | 10-2u=4 |